Marketing Strategy of Presto Milkfish at UD Rindang Hj Suryati with Blue Ocean Strategy Approach - Khoiryyah, Maftuhatul; Dwi Aulia Puspitaningrum (Jurnal Pertanian, 2025)
UD Rindang Hj Suryati is a presto milkfish producer in Juwana District. High competition followed by non-optimal social media management has an impact on the narrow market reach. This study aims to identify the internal and external factors of UD Rindang Hj Suryati to formulate a strategy that is in accordance with the company’s position; analyze the best marketing strategy for UD Rindang Hj Suryati’s presto milkfish products using the Blue Ocean Strategy approach. This type of research is quantitative with descriptive analysis through case studies. The method of determining respondents consists of purposive for internal business respondents and non probability sampling for external respondents. Data collection methods through observation, interviews, questionnaires, FGDs and documentation. The analysis techniques used, namely using IFE and EFE analysis, IE Matrix, and Blue Ocean Strategy. The results showed that UD Rindang Hj Suryati has the highest strengths, namely having MUI halal certification and using traditional production processes. The highest weakness is unstructured online marketing. The highest opportunity is the close and abundant availability of raw materials, and receiving orders directly or indirectly. The highest threat is that there is no expedition that supports the delivery of wet products. Based on the IE matrix, UD Rindang Hj Suryati is in quadrant 4 so the right strategy is an intensive strategy. The formulation of strategies with the Blue Ocean Strategy approach, namely increasing branding and engagement through Instagram; increasing labor competence in creating product and service innovations to consumers; improving visual packaging design; creating vacuum milkfish product innovations; and opening a market place as a means of selling products.